Nietzsche's political skepticism - Shaw, Tamsin, 1970- (Princeton University Press, 2007)
Political theorists have long been frustrated by Nietzsche's work. Although he develops profound critiques of morality, culture, and religion, it is very difficult to spell out the precise political implications of his insights. He himself never did so in any systematic way. In this book, Tamsin Shaw claims that there is a reason for this: Nietzsche's insights entail a distinctive form of political skepticism. Shaw argues that the modern political predicament, for Nietzsche, is shaped by two important historical phenomena. The first is secularization, or the erosion of religious belief, and the fragmentation of moral life that it entails. The second is the unparalleled ideological power of the modern state. The promotion of Nietzsche's own values, Shaw insists, requires resistance to state ideology. But Nietzsche cannot envisage how these values might themselves provide a stable basis for political authority; this is because secular societies, lacking recognized normative expertise, also lack a reliable mechanism for making moral insight politically effective. --From publisher's description.